A system‐wide assessment of forest biomass production, markets, and carbon. Issue 2 (29th November 2022) - Favero, Alice; Daigneault, Adam; Sohngen, Brent; Baker, Justin
Abstract: This study examines the effects of supplying forest biomass on forest ecosystem services and goods with a dynamic systems model. This unique analysis models dynamic trade and investments in forestry, thereby capturing price changes from increased forest biomass demand on current and future flows of forest ecosystem services and natural capital stocks. Forests across the globe are interconnected through timber and forest biomass markets, which influence forest management decisions, land rents, and policy responses. Results indicate that expanding forest biomass consumption, even at relatively low levels, will have important impacts on ecosystem services, particularly the benefits of terrestrial carbon sequestration and timber outputs. Increased forest biomass production can be achieved with smaller impacts on ecosystem services through policies targeting natural forest preservation. However, policies that encourage residual biomass use for energy or discourage forest plantation expansion could potentially compromise carbon benefits. Abstract : This study examines the effects of supplying forest biomass on forest ecosystem services and goods with a dynamic systems model. Results indicate that expanding forest biomass consumption, even at relatively low levels, will have important impacts on ecosystem services, particularly the benefits of terrestrial carbon sequestration and timber outputs. Forest biomass can be supplied without compromising future forest ecosystem services and goods under specific policy constraints.